If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5n+38=-6(7n+6)
We move all terms to the left:
-5n+38-(-6(7n+6))=0
We calculate terms in parentheses: -(-6(7n+6)), so:We get rid of parentheses
-6(7n+6)
We multiply parentheses
-42n-36
Back to the equation:
-(-42n-36)
-5n+42n+36+38=0
We add all the numbers together, and all the variables
37n+74=0
We move all terms containing n to the left, all other terms to the right
37n=-74
n=-74/37
n=-2
| 2x-1+7x+15=4x-1 | | -614=(-264)-(3h-581) | | 2(4z-17)=3(z+6) | | 6-9x=6x-10x-21 | | -9x-86=199+10x | | -4/5p+15=3/5 | | 8=3.75x+15 | | -4n+6=-2n-16 | | 3.75x+15=8 | | 5(x+9)=95 | | 61=3(7-5a)-5(a-4) | | 2(6c-3)=24 | | 6(3x+37)+7(x+44)=15 | | -614=(-3432)-(3h-581) | | 3/4(5x+20)=8 | | x=2(3.3)(3.14) | | 2(8x+48)=64 | | 4x-12=-5x+15 | | 12+5x=8+4(1-7x) | | 9(n/5)=9÷(n/5) | | (3+y/2)=6 | | .18y+.08(y+3000)=2580 | | 110+32h=590 | | 6.6+1.1n=4.18 | | 1.5x+1.67=2.57 | | 8x+4=6x+66x+6 | | 2t^2-14t+5=0 | | 8x+4= 6x+66x+6 | | -5+4n=-13 | | 6(x-3)/4+1=-11 | | 18d-10=6 | | (x-34)x15=0 |